The Predictive Role of Intraoperative Blood Transfusion Components in the Prognosis of Heart Transplantation - Yidan Zheng; Yidan Zheng; Li Xu; Li Xu; Ziwen Cai; Jingrong Tu; Jingrong Tu; Yuqi Liu; Yixuan Wang; Yixuan Wang; Si Chen; Si Chen; et al. (Frontiers in Cardiovascular Medicine, 2022)
PurposeTo evaluate the influence of transfusion amount of blood components on the prognosis of patients after heart transplantation (HTx).MethodsFrom 1 January 2015 to 31 December 2020, 568 patients underwent HTx in our institute. A total of 416 recipients with complete datasets were enrolled in the study for final statistical analysis according to the inclusion criteria. The optimal cut-off values for intraoperative transfusion of red blood cell (RBC), platelet, and plasma were determined with receiver operating curve analysis. Univariate and multivariate Cox regression analyses were applied to compare baseline data of patients divided by the transfusion amounts of RBC, platelet, and plasma. Propensity score matching was used to enable the direct comparison of outcomes.ResultsThe Kaplan–Meier analysis revealed that transfusion amounts of RBC and plasma were independently associated with overall mortality, increased intensive care unit stay time, and major adverse events after transplantation. The multivariate Cox regression analysis suggested that neurological complications (p = 0.001), liver damage (p = 0.011), and respiratory complications (p = 0.044) were independent risk factors for overall mortality after HTx. Combining indicators presented a good predicting effect of peritransplant period mortality (AUC = 0.718).ConclusionThe mortality of HTx was significantly related to the high-amount transfusion of RBC and plasma. Comprehensively considering the components of blood transfusion obtained better predictive results of peritransplant period survival than solely considering a single component.